Serum Vitamin D Levels in Neonates and Their Mothers at Birth: A Comparative Analysis Highlighting Need for Therapeutic Strategies - Hafsa Khaliq; Arshad Parvez Malik; Ihsan Ullah; Waqar Hayat; Muhammad Saleh Faisal; Tabinda Shadab (Journal of Rawalpindi Medical College)
Objective: Objective: The study was conducted to examine serum vitamin D levels in preterm and full-term neonates and their mothers at birth to explore potential associations.